Biosynthesis of silver nanoparticles from Citrobacter freundii as antibiofilm agents with their cytotoxic effects on human cells - Shakhatreh, MAK; Al-Rawi, OF; Swedan, SF; Alzoubi, KH; Khabour, OF; Al-Fandi, M (Bentham Science Publishers, 2021)
Background: Nanomaterials have recently been identified for their potential benefits in the areas of medicine and pharmaceuticals. Among these nanomaterials, silver nanoparticles (Ag-NPs) have been widely utilized in the fields of diagnostics, antimicrobials, and catalysis.